Unlocking the Potential of Paper Mulberry Powder in Cherry Valley Ducks: Impacts on Growth, Serum Biochemistry, and Cecum Microbiome - Yi Xiong; Chu Tang; Xuekai Wang; Yongsheng Wang; Fuyu Yang (Animals)
This study investigates the effects of incorporating paper mulberry (Broussonetia papyrifera L.) powder into the diets of Cherry Valley ducks on growth performance, serum biochemistry, and the gut microbiome. A total of 350 14-day-old male Cherry Valley ducks were randomly assigned to five groups receiving diets with 0%, 4%, 6%, 8%, and 10% paper mulberry powder for 42 days. Growth performance, meat quality, serum immunity, and cecal microbial composition were assessed. The results showed no significant differences in average daily feed intake and feed conversion ratio among treatments, with the 6% paper mulberry group showing the highest average daily gain (79.73 g) (p < 0.05). Meat quality parameters, including color, drip loss, cooking loss, and shear force, were not significantly affected by paper mulberry powder supplementation, while the 8% paper mulberry group showed the highest pH24 value (5.47) (p < 0.05). Serum biochemistry revealed increased total protein (G0, G4, G6, G8, and G10: 41.50, 44.47, 45.58, 45.67, and 45.85 g/L, respectively), albumin (G0, G4, G6, G8, and G10: 18.61, 19.56, 20.29, 20.2, and 20.39 g/L, respectively), total cholesterol (G0, G4, G6, G8, and G10: 5.31, 4.96, 5.37, 5.53, and 5.59 mmol/L, respectively), and high-density lipoprotein cholesterol (HDL) in ducks fed 6%, 8%, and 10% paper mulberry powder, with lower alanine aminotransferase (ALT), aspartate aminotransferase (AST), and total bilirubin (TBI) in the 8% and 10% groups (p < 0.05). Cecal microbial diversity was enhanced with paper mulberry powder, particularly in the 6% group, which showed increased Bacteroides abundance (p < 0.05). Supplementing duck diets with 6% paper mulberry powder increased average daily gain, without adversely affecting meat quality and health, suggesting its potential as a sustainable feed ingredient in the duck meat industry.